Polyamide composite and method for producing the same

CN122958853APending Publication Date: 2026-10-23CATHAY BIOTECH INC +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510505812.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]中国专利CN107974076A和CN112194893 B分别提供了一种包含尼龙树脂、聚酮树脂、阻燃剂、阻燃协效剂、相容剂、短切纤维、抗氧剂和润滑剂等的增强阻燃PA6/POK合金材料,该材料的吸水率相较传统PA6增强阻燃材料有所下降,使该材料可以应用于某些湿度较大的领域,但因树脂基体中引入了POK,导致制备的复合材料整体力学性能较差,极大限制了其应用范围

Benefits of technology

[0037](1)本发明的聚酰胺复合材料具有吸水率低、耐高温、耐水解、阻燃性好、力学性能优异、双85处理保持率高等的特点,可极大拓宽生物基聚酰胺在多个领域中的应用,包括电子电气、新能源储能端板、隔热条等;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to a kind of polyamide composite and its preparation method, the polyamide composite has the characteristics such as low water absorption, high temperature resistance, hydrolysis resistance, good flame retardancy, excellent mechanical properties, high double 85 processing retention rate, can greatly widen the application of bio-based polyamide in multiple fields, including electronic and electrical, new energy storage end plate, heat insulation strip etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite materials, and particularly relates to a polyamide composite material and its preparation method. Background Technology

[0002] Polyamide (Nylon) materials are widely used in various fields due to their excellent comprehensive properties. Among them, PA6 and PA66 are the most widely used, exhibiting excellent mechanical properties and heat resistance. However, traditional ordinary nylon materials also have some shortcomings. Their glass fiber (GF) reinforced materials easily absorb water in aqueous environments, resulting in poor product dimensional stability. Furthermore, they are prone to cracking due to high-temperature hydrolysis and alcoholysis, making it difficult to meet the standard requirements of related applications.

[0003] Furthermore, most nylon on the market is produced using petrochemical methods, resulting in high market usage and consumption, which does not align with the trend towards green environmental protection and sustainable development. Moreover, with increasing global awareness of safety and environmental protection, people have higher and higher requirements for fire safety and flame retardancy in products. Polyamide, as a typical organic polymer material, has a low oxygen index and can be ignited upon contact with a flame, producing a large number of molten droplets and releasing significant heat and gases during combustion. Therefore, flame retardant treatment is an essential step when applying polyamide to products with fire safety requirements, such as electronics, automobiles, and new energy products.

[0004] Chinese patents CN107974076A and CN112194893 B respectively provide a reinforced flame-retardant PA6 / POK alloy material containing nylon resin, polyketone resin, flame retardant, flame retardant synergist, compatibilizer, chopped fibers, antioxidant, and lubricant. The water absorption rate of this material is lower than that of traditional PA6 reinforced flame-retardant materials, which allows it to be used in some high-humidity areas. However, the introduction of POK into the resin matrix results in poor overall mechanical properties of the prepared composite material, which greatly limits its application range.

[0005] CN107298855A discloses a hydrolysis-resistant and alcoholysis-reinforced nylon material and its preparation method. It uses a compound anti-hydrolysis agent and selects long-chain nylon as the base material. However, it does not involve the flame retardant properties of the material. Furthermore, long-chain nylon has poor high-temperature resistance and some mechanical properties, which cannot meet the needs of multiple fields.

[0006] Therefore, existing polyamide composite materials need to be improved. Summary of the Invention

[0007] To overcome at least one of the defects of the prior art, in a first aspect, one embodiment of the present invention provides a polyamide composite material, characterized in that, based on 100 parts by weight of polyamide resin, the amount of modified glass fiber added is 30 to 300 parts by weight, for example 50 parts by weight, 100 parts by weight, 150 parts by weight, 200 parts by weight, 250 parts by weight, etc., and the amount of composite flame retardant added is 5 to 50 parts by weight, for example 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, etc. The amounts of the following additives are available in parts by weight: 30 parts by weight, 35 parts by weight, 40 parts by weight, and 45 parts by weight. The amount of hydrolysis resistant agent added is 0.4–2.0 parts by weight, for example, 0.5 parts by weight, 1.0 parts by weight, and 1.5 parts by weight. The amount of antioxidant added is 0.8–2.5 parts by weight, for example, 1.0 parts by weight, 1.5 parts by weight, and 2.0 parts by weight. The amount of lubricant added is 0.8–3.0 parts by weight, for example, 1.0 parts by weight, 1.5 parts by weight, 2.0 parts by weight, and 2.5 parts by weight.

[0008] The polyamide resin comprises amide-bonded polyamide units AB and AC derived from monomer units A, B and C, wherein monomer unit A is derived from pentanediamine and / or hexanediamine, monomer unit B is derived from terephthalic acid, and monomer unit C is derived from long-chain dicarboxylic acid.

[0009] In some embodiments, based on 100 parts by weight of polyamide resin, the amount of modified glass fiber added is 50 to 200 parts by weight, the amount of composite flame retardant added is 10 to 40 parts by weight, the amount of hydrolysis resistant agent added is 0.6 to 1.5 parts by weight, the amount of antioxidant added is 1.2 to 2.0 parts by weight, and the amount of lubricant added is 1.2 to 2.4 parts by weight.

[0010] In some embodiments, the long-chain dicarboxylic acid is a dicarboxylic acid with the chemical formula HOOC(CH2)nCOOH, wherein n≥8, and further n=8~16; and / or, the pentanediamine is a bio-based pentanediamine.

[0011] In some embodiments, the polyamide resin has a melting point of 200–320°C, such as 220°C, 240°C, 260°C, 280°C, 300°C, etc.

[0012] In some embodiments, the relative viscosity of the polyamide resin is 2.0 to 2.8, for example 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, etc.

[0013] In some embodiments, the molar ratio of AB and AC structural units in the polyamide resin is 0.5 to 5.0, for example, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, etc.

[0014] In some embodiments, the modified glass fiber has a diameter of 8–15 μm and a length of 2.0–5.0 mm.

[0015] In some embodiments, the modified glass fiber comprises glass fiber modified by at least one of silane coupling agents, aluminate coupling agents, and titanate coupling agents.

[0016] In some embodiments, the hydrolysis-resistant agent includes one or more of carbodiimide and polycarbodiimide.

[0017] In some embodiments, the composite flame retardant includes an organic hypophosphite flame retardant, an organic polyphosphate flame retardant, and an inorganic flame retardant synergist.

[0018] In some embodiments, the organic hypophosphite flame retardant is a linear or branched organic hypophosphite containing alkyl and / or aryl groups having 1 to 6 carbon atoms. The organic hypophosphite cation is selected from one or more combinations of alkali metals, Al, Zn, Fe, or Ti. The organic hypophosphite flame retardant is preferably an organic hypophosphite containing alkyl groups having 1 to 4 carbon atoms. The organic hypophosphite cation is preferably Al or Zn, and more preferably diethylaluminum hypophosphite.

[0019] In some embodiments, the organopolyphosphate flame retardant includes melamine polyphosphate.

[0020] In some embodiments, the inorganic flame retardant synergist includes one or a combination of several of ultrafine magnesium hydroxide, ultrafine aluminum hydroxide, ultrafine iron hydroxide, ultrafine zirconium hydroxide, zinc borate, sodium borate, magnesium borate, calcium borate, potassium borate, and lithium borate, and is more preferably one or a combination of several of zinc borate, ultrafine magnesium hydroxide, and ultrafine zirconium hydroxide.

[0021] In some embodiments, the lubricant includes one or more of higher fatty alcohols, fatty acid esters, higher fatty acids, fatty amides, paraffin wax, etc., preferably one or more of N,N-ethylene bis-stearamide, erucamide, and stearamide.

[0022] In some embodiments, the antioxidant includes one or more of hindered phenolic antioxidants (such as 245, 1010, 1098) and phosphite antioxidants (such as 9228, 168), preferably a combination of 1098 and 9228.

[0023] In some embodiments, the mass ratio of the composite flame retardant to the hydrolysis resistant agent is (20-40):1, for example 22:1, 24:1, 26:1, 28:1, 30:1, 32:1, 34:1, 36:1, 38:1, etc.

[0024] In some embodiments, the saturated water absorption rate of the polyamide composite material is 0.5 to 2.0%, preferably 0.5 to 1.5%, for example 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, etc.

[0025] In some embodiments, the tensile strength of the polyamide composite material is 120-300 MPa, preferably 130-250 MPa, such as 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, etc.

[0026] In some embodiments, the flexural strength of the polyamide composite material is 200-350 MPa, preferably 220-300 MPa, such as 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa, 320 MPa, 340 MPa, etc.

[0027] In some embodiments, the simply supported beam impact strength of the polyamide composite material is 5–50 kJ / m. 2 Preferably, it is 5.5–40 kJ / m 2 For example, 10kJ / m 2 15kJ / m 2 20kJ / m 2 25kJ / m 2 30kJ / m 2 35kJ / m 2 40kJ / m 2 45kJ / m 2 wait.

[0028] In some embodiments, the flame retardancy of the polyamide composite material is at least at level V1 of UL94 0.8mm.

[0029] In some embodiments, after boiling in water at 80°C for 96 hours, the polyamide composite material has a tensile strength of 110–280 MPa, preferably 130–250 MPa, such as 120 MPa, 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, etc., and a flexural strength of 180–320 MPa, preferably 210–250 MPa, such as 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa, etc.

[0030] In some embodiments, after boiling in water at 80°C for 288 hours, the polyamide composite material has a tensile strength of 100–250 MPa, preferably 120–210 MPa, such as 120 MPa, 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, etc., and a flexural strength of 150–280 MPa, preferably 200–250 MPa, such as 120 MPa, 140 MPa, 160 MPa, 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, etc.

[0031] In some embodiments, the polyamide composite material retains 50-70% of its double 85 2000h tensile strength, preferably 60-70%, such as 55%, 60%, 65%, etc.

[0032] In some embodiments, the heat distortion temperature of the polyamide composite material is 200-280°C, preferably 230-280°C, such as 220°C, 240°C, 260°C, etc.

[0033] In a second aspect of the present invention, the present invention provides a method for preparing the polyamide composite material described in the first aspect, the method comprising: adding polyamide resin to the main feed port of an extruder, adding a flame retardant, an antioxidant, a hydrolysis resistant agent and a lubricant to a first side feed port, adding modified glass fiber to a second side feed port, melt extruding, cooling, pelletizing, and obtaining the polyamide composite material.

[0034] In some embodiments, the melt extrusion apparatus is a twin-screw extruder, wherein the screw length-to-diameter ratio of the twin-screw extruder is (40-50):1, the extruder barrel temperature is 200-350℃, the screw speed is 200-500rpm, and the capacity is 20-50kg / h.

[0035] In some embodiments, the cooling device is a cooling water tank or an air-cooled conveyor belt, preferably an air-cooled conveyor belt.

[0036] The beneficial effects of this invention are as follows:

[0037] (1) The polyamide composite material of the present invention has the characteristics of low water absorption, high temperature resistance, hydrolysis resistance, good flame retardancy, excellent mechanical properties, and high retention rate of double 85 treatment, which can greatly broaden the application of bio-based polyamide in multiple fields, including electronics and electrical, new energy storage end plates, heat insulation strips, etc.

[0038] (2) The polyamide composite material of the present invention can achieve excellent hydrolysis resistance, fire retardant and mechanical properties without or with only a small amount of halogen-free flame retardant system and without or with only a small amount of hydrolysis resistant agent, so that it can meet the needs of different plastic products. Detailed Implementation

[0039] Typical embodiments embodying the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various variations in different embodiments without departing from the scope of the present invention, and the description herein is for illustrative purposes only and not intended to limit the present invention.

[0040] The following describes a polyamide composite material and its preparation method according to an embodiment of the present invention, with reference to specific examples. The raw materials and testing methods involved in each embodiment and comparative example are as follows.

[0041] raw material

[0042] 1. Bio-based PA510 / 5T resin A: The mass ratio of 510 to 5T is 1:1, the melting point is 259℃, and the relative viscosity is 2.38.

[0043] Bio-based PA510 / 5T resin B: The mass ratio of 510 to 5T is 2:3, the melting point is 288℃, and the relative viscosity is 2.31.

[0044] The bio-based PA512 / 5T resin C has a mass ratio of 512 to 5T of 1:1, a melting point of 264℃, and a relative viscosity of 2.40.

[0045] 2. Modified glass fiber: 10μm in diameter and 3mm in length, grade ECS301HP, purchased from Chongqing International Composite Materials Co., Ltd.

[0046] 3. Composite flame retardants: Diethyl aluminum hypophosphite was purchased from Zhejiang Chuanhua Chemical Group, melamine polyphosphate was purchased from Zhejiang Xusen Flame Retardant Co., Ltd., and zinc borate was purchased from Zhejiang Xusen Flame Retardant Co., Ltd.

[0047] 4. Hydrolysis resistant agent: Polymeric carbodiimide was purchased from Lanxess Chemicals (China) Co., Ltd.

[0048] 5. Antioxidant 1098 was purchased from BASF AG, Germany, and antioxidant 9228 was purchased from Dover Chemical Company, USA.

[0049] 6. The lubricant erucamide was purchased from Jiangxi Weike Oil & Chemical Co., Ltd.

[0050] Test methods

[0051] 1) Bending test: The test shall be conducted in accordance with the standard ISO 178-2010.

[0052] 2) Tensile test: The test shall be conducted in accordance with the standard ISO 572-1-2012.

[0053] 3) Impact test: Notched impact test of a simply supported beam, in accordance with test standard ISO 179-1-2000.

[0054] 4) Flame retardancy rating test: The flame retardancy performance of the sample was tested according to the relevant standard of GB / T 2408-2021. The sample thickness was 0.8mm. The UL-94 flame retardancy ratings for plastics include: NG, V-2, V-1 and V-0. NG indicates that it does not meet the UL criteria.

[0055] 5) Water absorption: Measured according to the relevant standards of GB / T1034-2008.

[0056] 6) Heat distortion temperature (HDT): Tested in accordance with national standard GB / T 1634.2-2004.

[0057] 7) Hydrolysis resistance: The test is conducted in accordance with the national standard GB / T 11547-2008.

[0058] 8) Dual 85 performance retention rate: Tested according to national standard GB / T 2423.50-2012.

[0059] Example 1

[0060] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA510 / 5T resin A, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 19.2 parts by weight of diethyl aluminum hypophosphite, 4.8 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 1.0 part by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0061] Polyamide resin is added to the main feed port of a twin-screw extruder, a composite flame retardant, antioxidant, hydrolysis resistant agent, and lubricant are added to the first feed port, and modified glass fiber is added to the second feed port. The mixture is melt-extruded, cooled, and pelletized to obtain a polyamide composite material. The twin-screw extruder has a screw length-to-diameter ratio of 48:1, a barrel temperature of 300℃, a main screw speed of 250 rpm, and a production capacity of 35 kg / h.

[0062] Example 2

[0063] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA510 / 5T resin A, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 24 parts by weight of diethyl aluminum hypophosphite, 6 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 1.5 parts by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0064] Everything else is the same as in Example 1.

[0065] Example 3

[0066] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA510 / 5T resin A, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 16 parts by weight of diethyl aluminum hypophosphite, 4 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 0.6 parts by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0067] Everything else is the same as in Example 1.

[0068] Example 4

[0069] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA510 / 5T resin B, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 19.2 parts by weight of diethyl aluminum hypophosphite, 4.8 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 1.0 part by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0070] The extruder barrel temperature was 310°C, and other conditions were the same as in Example 1.

[0071] Example 5

[0072] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA510 / 5T resin B, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 24 parts by weight of diethyl aluminum hypophosphite, 6 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 1.5 parts by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0073] The rest is the same as in Example 4.

[0074] Example 6

[0075] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA510 / 5T resin B, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 16 parts by weight of diethyl aluminum hypophosphite, 4 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 0.6 parts by weight of polymeric carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0076] The rest is the same as in Example 4.

[0077] Example 7

[0078] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA512 / 5T resin C, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 19.2 parts by weight of diethyl aluminum hypophosphite, 4.8 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 1.0 part by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0079] The extruder barrel temperature was 295°C, and other conditions were the same as in Example 1.

[0080] Example 8

[0081] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA512 / 5T resin C, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 24 parts by weight of diethyl aluminum hypophosphite, 6 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 1.5 parts by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0082] The rest is the same as in Example 7.

[0083] Example 9

[0084] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA510 / 5T resin C, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 16 parts by weight of diethyl aluminum hypophosphite, 4 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 0.6 parts by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0085] The rest is the same as in Example 7.

[0086] Comparative Example 1

[0087] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA510 / 5T resin A, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 19.2 parts by weight of diethyl aluminum hypophosphite, 4.8 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 0.6 parts by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0088] Everything else is the same as in Example 1.

[0089] Comparative Example 2

[0090] The polyamide composite material is formulated as follows: 100 parts by weight of bio-based PA512 / 5T resin C, 0.6 parts by weight of antioxidant 1098, 0.8 parts by weight of antioxidant 9228, 11.2 parts by weight of diethyl aluminum hypophosphite, 2.8 parts by weight of melamine polyphosphate, 4 parts by weight of zinc borate, 1.0 part by weight of polymerized carbodiimide, 1.5 parts by weight of erucamide, and 60 parts by weight of modified glass fiber.

[0091] The rest is the same as in Example 7.

[0092] The polyamide composite materials prepared in each embodiment and comparative example were subjected to relevant performance tests according to the aforementioned method, and the results are shown in Table 1.

[0093] Table 1

[0094]

[0095] Based on the above embodiments and comparative results:

[0096] (1) The polyamide composite material in each embodiment has good mechanical properties, low water absorption, high temperature resistance, high flame retardancy, and performance retention rate >90% after boiling in water at 80℃ for 288h (excellent hydrolysis resistance). Moreover, the performance retention rate is very high (about 65%) after double 85 treatment for 2000h. It is a bio-based flame retardant composite material with excellent comprehensive performance.

[0097] (2) According to the comparative examples, when the ratio of composite flame retardant to hydrolysis resistant agent in the system exceeds (20~40) / 1, the hydrolysis resistance of the composite material is very poor, the aging resistance of the material is poor, and the mechanical properties are also affected, which greatly limits its application scenarios.

[0098] (3) As can be seen from Examples 1-3, when the amount of composite flame retardant added reaches about 14.6%, the flame retardant grade of the material can reach 0.8mm V-0, and the composite flame retardant / hydrolysis resistant agent is in the range of (20~40) / 1, the composite material has good hydrolysis resistance. This rule can also be obtained from Examples 7-9.

[0099] (4) As can be seen from Examples 4-6, when the content of “T” in the resin matrix increases, the amount of composite flame retardant added only needs to be about 12.8%, and the flame retardant grade of the material can reach 0.8mm V0, while its overall mechanical strength is improved.

[0100] (5) As can be seen from Examples 7-9, when the long carbon chain dicarboxylic acid in the resin matrix is ​​dodecanoic acid, due to its long chain length, there are fewer hydrogen bonds in the material, resulting in a lower water absorption rate of the composite material; however, due to the reduction of the "T" content in the matrix, the overall mechanical strength of the material decreases, but the toughness is enhanced (the impact strength increases), while still maintaining good flame retardant properties.

[0101] As can be seen from the above conclusions, this composite material can be applied to different market sectors according to different needs, and it requires less flame retardant, resulting in lower material costs and making it easier to promote in the market.

[0102] Unless otherwise specified, the terms used in this invention have the meanings commonly understood by those skilled in the art.

[0103] The embodiments described in this invention are for illustrative purposes only and are not intended to limit the scope of protection of this invention. Those skilled in the art can make various other substitutions, changes and improvements within the scope of this invention. Therefore, this invention is not limited to the above embodiments, but is only defined by the claims.

Claims

1. A polyamide composite material, characterized in that, Based on 100 parts by weight of polyamide resin, the amount of modified glass fiber added is 30–300 parts by weight, the amount of composite flame retardant added is 5–50 parts by weight, the amount of hydrolysis resistant agent added is 0.4–2.0 parts by weight, the amount of antioxidant added is 0.8–2.5 parts by weight, and the amount of lubricant added is 0.8–3.0 parts by weight. The polyamide resin comprises amide-bonded polyamide units AB and AC derived from monomer units A, B and C, wherein monomer unit A is derived from pentanediamine and / or hexanediamine, monomer unit B is derived from terephthalic acid, and monomer unit C is derived from long-chain dicarboxylic acid.

2. The polyamide composite material according to claim 1, characterized in that, Based on 100 parts by weight of polyamide resin, the amount of modified glass fiber added is 50–200 parts by weight, the amount of composite flame retardant added is 10–40 parts by weight, the amount of hydrolysis resistant agent added is 0.6–1.5 parts by weight, the amount of antioxidant added is 1.2–2.0 parts by weight, and the amount of lubricant added is 1.2–2.4 parts by weight; and / or, The long-chain dicarboxylic acid has the chemical formula HOOC(CH2). n Dicarboxylic acids of COOH, wherein n≥8, and further n=8~16; and / or, The pentanediamine is a bio-based pentanediamine.

3. The polyamide composite material according to claim 1, characterized in that, The polyamide resin has a melting point of 200–320°C; and / or, The relative viscosity of the polyamide resin is 2.0 to 2.8; and / or, The mass ratio of AB and AC structural units in the polyamide resin is 0.5 to 5.

0.

4. The polyamide composite material according to claim 1, characterized in that, The modified glass fibers have a diameter of 8–15 μm and a length of 2.0–5.0 mm; and / or, The modified glass fiber comprises glass fiber modified with at least one of silane coupling agents, aluminate coupling agents, and titanate coupling agents; and / or, The hydrolysis-resistant agent includes one or more of carbodiimide and polycarbodiimide.

5. The polyamide composite material according to claim 1, characterized in that, The composite flame retardant includes an organic hypophosphite flame retardant, an organic polyphosphate flame retardant, and an inorganic flame retardant synergist; The organic hypophosphite flame retardant is a linear or branched organic hypophosphite containing alkyl and / or aryl groups with 1 to 6 carbon atoms. The organic hypophosphite cation is selected from one or more combinations of alkali metals, Al, Zn, Fe, or Ti. Preferably, the organic hypophosphite flame retardant contains alkyl groups with 1 to 4 carbon atoms, and the organic hypophosphite cation is preferably Al or Zn, more preferably diethylaluminum hypophosphite; and / or... The organopolyphosphate flame retardant includes melamine polyphosphonate; and / or The inorganic flame retardant synergist includes one or a combination of several of ultrafine magnesium hydroxide, ultrafine aluminum hydroxide, ultrafine iron hydroxide, ultrafine zirconium hydroxide, zinc borate, sodium borate, magnesium borate, calcium borate, potassium borate, and lithium borate, and is more preferably one or a combination of several of zinc borate, ultrafine magnesium hydroxide, and ultrafine zirconium hydroxide.

6. The polyamide composite material according to claim 1, characterized in that, The lubricant comprises one or more of the following: higher fatty alcohols, fatty acid esters, higher fatty acids, fatty amides, paraffin wax, etc., preferably one or more of N,N-ethylene bis-stearamide, erucamide, and stearamide; and / or, The antioxidants include one or more of hindered phenolic antioxidants and phosphite antioxidants, preferably a combination of 1098 and 9228.

7. The polyamide composite material according to claim 1, characterized in that, The mass ratio of the composite flame retardant to the hydrolysis resistant agent is (20-40):

1.

8. A method for preparing a polyamide composite material according to any one of claims 1-7, characterized in that, The saturated water absorption rate of the polyamide composite material is 0.5–2.0%, preferably 0.5–1.5%; and / or, The tensile strength is 120–300 MPa, preferably 130–250 MPa; and / or, The flexural strength is 200–350 MPa, preferably 220–300 MPa; and / or, The impact strength of a simply supported beam is 5–50 kJ / m. 2 Preferably, it is 5.5–40 kJ / m 2 ; and / or, Flame retardancy is UL94 0.8mm, reaching at least V1 level; and / or, After boiling in water at 80℃ for 96 hours, the tensile strength is 110–280 MPa, preferably 130–250 MPa, and the flexural strength is 180–320 MPa, preferably 210–250 MPa; and / or, After boiling in water at 80℃ for 288 hours, the tensile strength is 100–250 MPa, preferably 120–210 MPa, and the flexural strength is 150–280 MPa, preferably 200–250 MPa; and / or, The tensile strength retention rate of double 85 after 2000 hours is 50-70%, preferably 60-70%; and / or, The heat distortion temperature is 200–280℃, preferably 230–280℃.

9. A method for preparing the polyamide composite material according to any one of claims 1-8, characterized in that, The method includes: adding polyamide resin to the main feed port of an extruder, adding flame retardant, antioxidant, hydrolysis resistant agent and lubricant to the first side feed port, adding modified glass fiber to the second side feed port, melting and extruding, cooling, pelletizing, and obtaining polyamide composite material.

10. The method according to claim 9, characterized in that, The melt extrusion device is a twin-screw extruder, wherein the screw length-to-diameter ratio of the twin-screw extruder is (40-50):1, the extruder barrel temperature is 200-350℃, the screw speed is 200-500rpm, and the capacity is 20-50kg / h; and / or, The cooling device is a cooling water tank or an air-cooled conveyor belt, preferably an air-cooled conveyor belt.

Citation Information

Patent Citations

  • Hydrolysis and alcoholysis-resisting reinforced nylon material and preparation method thereof

    CN107298855A

  • Reinforced flame-retarding PA6 / POK (Polyamide 6 / Polyketone) alloy material and preparation method thereof

    CN107974076A

  • A hydrolysis-resistant, flame-retardant PA6-POK alloy material and its preparation method

    CN112194893B